Factor Analysis of Dengue Hemorrhagic Fever - Nazhiifah, Nisriina; Sumargo, Bagus; Erdien, Fareka; Kirana, Siti Julpia; Rahayu, Widyanti; Mulyono (LPPM Universitas Negeri Jakarta, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus. DHF cases have always been a serious problem every year in Central Java. This study aimed to determine the factors that cause Dengue Hemorrhagic Fever (DHF) in the province of Central Java because cases of DHF in the region become a serious problem every year. The method used for this research is Principal Component Analysis and Factor Analysis using secondary data from the Central Java Provincial Health Office in 2018. The results of the analysis show that 3 factors are causing DHF, namely the population participation factor in health, sanitation factors, and clean drinking water factors. This shows the importance of environmental education to increase population awareness in terms of healthy living and local government intervention is needed in environmental health projects, namely sanitation and clean drinking water This research only uses seven variables that are considered relevant, other variables that may also have an influence are not included in this analysis. This research focuses on a particular year that shows a decreasing trend in cases. This approach offers a fresh and distinct perspective on understanding the dynamics of dengue fever and the factors that contribute to its reduction.